Maternal Serum Zinc level in pregnant women with second trimester induced abortion with anencephalic fetus - Shalal, .Maad M.; Al-Bassam, Anwar N.; Alwan, Buthaina A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Neural tube defects (NTD) are group of heterogeneous and complex congenital anomalies of the CNS. Commonly included in this group anencephaly, spina bifida and encephaloceles. Anencephaly is the most severe defect; it is always lethal and results in stillbirth or early neonatal demise, is characterized by absence of the brain and cranium above the base of the skull and orbits Objective: The objective of this study is to assess the relationship between maternal serum zinc level and anencephaly occurrence in women with second -trimester induced abortion due to anencephalic fetus. Study design and setting: This study is a case- control study, carried out in Baghdad teaching hospital throughout the period between November 2008- November 2009. Patients and method: This study involves 33 pregnant women whose pregnancies were terminated for anencephaly in the second-trimester that was diagnosed by ultrasound the control group consisted of 66 matched to demographic and obstetrical characteristics and had normal ultrasonographic findings in second-trimester with documented normal fetal outcome. Zinc level determination was made using flame atomic absorption spectrophotometer (AAS). Results: Medication consumption during the first trimester of pregnancy has a significant relation with the occurrence of NTDs with a p – value = 0.027. Low serum Zinc level was found in 18 (54.5%) of the cases and 5 (7.6%) of the controls with p- value = 0.0001. There was a highly significant relationship between the presence of NTDs and low serum zinc level. Conclusions: In this study there was a significant association between NTDs and low serum zinc levels, adding to the evidence about the importance of nutritional and maternal health factors in the etiology of this disease.